Seeding-free inlet flow distortion measurements using filtered Rayleigh scattering: integration in a complex intake test facility - Migliorini, Matteo; Zachos, Pavlos K.; MacManus, David G.; Doll, Ulrich; Dues, Michael; Jonas, Steinbock J.; Dues, Fritz; Siswanto, Adi; Melnikov, Sergey M.; Röhle, Ingo (American Institute of Aeronautics and Astronautics (AIAA), 2024)
Highly integrated propulsion systems to achieve fuel savings and reduction of emissions in future aircrafts call for new measurement methods to assess inlet conditions at the engine fan face. Propulsion systems are expected to operate at higher levels of total pressure, total temperature, and swirl distortion due to flow interaction with aerodynamic surfaces and inherent flow distortion within convoluted intakes. Filtered Rayleigh Scattering (FRS) offers capability to assess all these quantities at once, and without the need of seeding particles which cannot be used for in-flight measurements. This paper aims at increasing the technology readiness level of this measurement technique through the application on a lab-scale S-duct diffuser tests and benchmark against Stereo-Particle Image Velocimetry (S-PIV) measurements. Methods to improve the optical integration and mitigate the effect of varying background conditions are hereby explored. Overall, this represents a step forward in the use of FRS as a turnkey solution for the testing and development phase of future propulsion systems.